Karen Fog Olwig: Global Culture, Island Identity: Continuity and Change in the Afro-Caribbean Community of Nevis - Eriksen, Thomas Hylland (Tidsskriftet Antropologi, 2019)
Karen Fog Olwig: Global Culture, Island Identity: Continuity and Change in the Afro-Caribbean Community of Nevis Anmeldes af Thomas Hylland Eriksen